2020
DOI: 10.3390/pharmaceutics12090808
|View full text |Cite
|
Sign up to set email alerts
|

Saturated Fatty Acid-Based In Situ Forming Matrices for Localized Antimicrobial Delivery

Abstract: In recent years, the world has faced the issue of antibiotic resistance. Methicillin-resistant Staphylococcus aureus (MRSA) is a significant problem in various treatments and control of infections. Biocompatible materials with saturated fatty acids of different chain lengths (C8–C18) were studied as matrix formers of localized injectable vancomycin HCl (VCM)-loaded antisolvent-induced in situ forming matrices. The series of fatty acid-based in situ forming matrices showed a low viscosity (5.47–13.97 cPs) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 91 publications
(107 reference statements)
8
24
0
Order By: Relevance
“…In contrast, a rosin nucleation-like formation was found from the solvent exchange between NMP and water inducing rosin phase separation. The nucleation was generated at the interaction of two phases, inducing the agglomeration of particles [ 12 , 37 ]. These interfacial phenomena could indicate the microscopic self-forming behavior of the rosin/LO complex using various solvents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, a rosin nucleation-like formation was found from the solvent exchange between NMP and water inducing rosin phase separation. The nucleation was generated at the interaction of two phases, inducing the agglomeration of particles [ 12 , 37 ]. These interfacial phenomena could indicate the microscopic self-forming behavior of the rosin/LO complex using various solvents.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the rosin/LO combination dissolved better in DMSO because of the low viscosity of the solution. When a solvent with a high potential to dissolve polymers is used, lower viscosity solutions are obtained [ 12 ]. For example, in situ forming gel based on bleach shellac dissolved in DMSO obtained a low viscosity when compared to that of in NMP and 2-pyrrolidone [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 shows the fluorescence micrographs with green and yellow regions corresponding to the agarose gel and the ISG formulation, respectively. Tracing sodium fluorescence as green color moving from the agarose was observed under a fluorescence microscope within a predetermined time [ 64 ]. The phase-separated networks of the ISG systems were attributed to the solvent exchange between these two phases.…”
Section: Resultsmentioning
confidence: 99%
“…Hexadecanoic acid is formed during fatty acid synthesis (lipogenesis). As a result, it is found in adipose tissue [1] and breast milk of humans [2]. Palmitic acid is used in cosmetic industries as well as in the manufacture of soaps.…”
Section: Introductionmentioning
confidence: 99%